(untitled) (International Journal of Engineering and Computer Science, 2017)
cloud computing is a storing and accessing data and programs over the Internet instead of computer’s hardware. Cloud computing is gaining popularity because it provides various on demand services which is location independent. Cloud user can store their data on cloud server remotely. So the data storage is resided with third party cloud service provider. In such situation, maintaining the privacy of user’s data from unauthorized users is not an easy task. Before storing the data on the cloud server, the data can be encrypted. Using privacy preserving public auditing, data hosting service also brings new security threats toward users data, thus making individuals or enterprisers still feel hesitant. Sometimes data owners lose ultimate control over the fate of their outsourced data so there is risk that availability and integrity of the data might be lost. To protect outsourced data in cloud storage against corruptions, adding fault tolerance to cloud storage together with data integrity checking and failure reparation. Due to lower repair bandwidth while providing fault tolerance Regenerating codes have gained popularity